2022
DOI: 10.3390/chemosensors10030106
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Quartz Crystal Microbalance Biosensors Based on the Molecular Imprinting Technique for Disease-Related Biomarkers

Abstract: The molecular imprinting technique is a quickly developing field of interest regarding the synthesis of artificial recognition elements that enable the specific determination of target molecule/analyte from a matrix. Recently, these smart materials can be successfully applied to biomolecule detection in biomimetic biosensors. These biosensors contain a biorecognition element (a bioreceptor) and a transducer, like their biosensor analogs. Here, the basic difference is that molecular imprinting-based biosensors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 169 publications
(177 reference statements)
0
9
0
Order By: Relevance
“…Chemically, MIPs are synthesized by bulk process where reaction occurs in a homogenous mixture [ 35 , 36 ]. Chemical interactions occurring between monomer and analyte may be through a non-covalent bond that can generate cavities on the bulk of the MIPs [ 37 , 38 , 39 , 40 , 41 ]. Research progress on MIP sensors for the detection of sucrose has demonstrated promising results in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, MIPs are synthesized by bulk process where reaction occurs in a homogenous mixture [ 35 , 36 ]. Chemical interactions occurring between monomer and analyte may be through a non-covalent bond that can generate cavities on the bulk of the MIPs [ 37 , 38 , 39 , 40 , 41 ]. Research progress on MIP sensors for the detection of sucrose has demonstrated promising results in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…As a counterpart to natural antibodies, the technique of epitope imprinting has shown a prospective application in fields such as sample treatment, protein purification, cancer diagnosis, chromatographic analysis, biomedical applications, drug delivery, biomarker detection etc. 108,109 In this section, a special emphasis has been given to the sensing applications of the epitope imprinted polymers. The various studies performed for biomarker detection employing epitope imprinted polymers have been described and listed in Table 1.…”
Section: Application Of Epitope Imprinted Polymers For the Electroche...mentioning
confidence: 99%
“…Furthermore, QCM has the ability to detect a broad variety of biomolecules, such as proteins, nucleic acids, peptides, oligonucleotides, hormones, etc. [ 45 ]. In particular, the rapid detection process and the high sensitivity of QCM systems make them attractive for the development of novel diagnostic tools.…”
Section: Sensing Principles Of Qcmmentioning
confidence: 99%